The Impact of Family Involvement on SMEs' Performance: Theory and Evidence. (29th December 2013) - De Massis, Alfredo; Kotlar, Josip; Campopiano, Giovanna; Cassia, Lucio
<x xml:space="preserve">Abstract</x> By complementing agency theory with behavioral assumptions, we explore the effects of family involvement on small and medium enterprises' (SMEs) performance. We identify three separate dimensions of family involvement and hypothesize nonlinear, direct, and interaction effects on the performance of an SME. The evidence on 787 SMEs suggests that an inverted U‐shaped relationship exists between family ownership and performance, and ownership dispersion among family members negatively affects performance. Balancing family and nonfamily members in the top management team (TMT) is found to be beneficial to SMEs' performance, but the family ratio in the TMT becomes crucial only at high levels of family ownership.